Evaluation of temperature on different wheelchair cushions using infrared thermography method - Bui, He Thong; Tao, Quang Bang; Lestriez, Philippe; Debray, Karl; Taiar, Redha; Hoang, Van Thanh (Journal of Mechanical Science and Technology, 2023)
Newly developed wheelchair cushions, nowadays, promise to offer more comfort and protection against injury for wheelchair users. Therefore, developing novel wheelchair cushions has become a real challenge for manufacturers in recent years. In particular, thermal properties of the wheelchair cushion and their effect on the user’s comfort are very important factors in the design and optimization. This paper reports the findings of an investigation into the thermal properties of wheelchair cushions using an infrared thermography system. The experimental results showed a variation in the temperature behavior of different trademarks of cushions depending on the heating zones and the C1 cushion made in TPU material has more advantages than the other cushions made in PU foam, pharmform, and visco-foam. The results and analysis from this research will help to find a better type of cushion and contribute to collecting useful medical information to prevent pressure ulcers for bedridden patients.
Keywords: Pressure ulcers; Temperature measurement; Thermal comfort; Thermography; Wheelchair cushion